New regimes of dispersion in microfluidics as mediated by travelling temperature waves. (9th October 2019) - Pal, Debashis; Chakraborty, Suman
Abstract : We unveil new regimes of dispersion in miniaturized fluidic devices, by considering fluid flow triggered by a travelling temperature wave. When a temperature wave travels along a channel wall, it alters the density and viscosity of the adjacent fluid periodically. Successive expansion–contraction of the fluid volume through a spatio-temporally evolving viscosity field generates a net fluidic current. Based on the temporal evolution of the axial dispersion coefficient, new regimes of dispersion—such as a short-time 'oscillating regime' and a large-time 'stable regime'—have been identified, which are absent in traditionally addressed flows through miniaturized fluidic devices. Our analysis reveals that the oscillation of axial dispersion persists until the variance of species concentration becomes equal to half of the square of the wavelength of the thermal wave. The time period of oscillation in the dispersion coefficient turns out to be a unique function of the thermal wavelength and net flow velocity induced by thermoviscous pumping. The results of this study are likely to contribute towards the improvement of microscale systems that are subjected to periodic temperature variations, including microreactors and DNA amplification devices.